TBIO-08. TUMOR MUTATIONAL BURDEN AND DRIVER MUTATIONS: FURTHER INSIGHT INTO THE GENOMIC LANDSCAPE OF PEDIATRIC BRAIN TUMORS. Issue 2 (22nd June 2018) - Patel, Roshal; Halligan, Katharine; Ramkissoon, Shakti; Ross, Jeffrey; Weintraub, Lauren
Abstract: Tumor mutational burden (TMB) and driver mutations are potential biomarkers to predict efficacy of immune checkpoint inhibitors (ICPI). Studies demonstrated malignant gliomas with high TMB in children and adults may preferentially benefit from treatment with ICPI. To characterize the association between TMB and known drivers in pediatric brain tumors, comprehensive genomic profiling (CGP) was performed on 723 pediatric (≤18 years) glioma samples using DNA extracted from 40 microns of formalin-fixed paraffin-embedded tissue. CGP utilized hybridization-captured, adaptor ligation based libraries sequenced to a mean coverage depth of >500X for up to 315 cancer-related genes. TMB was calculated as mutations per megabase and categorized as low (0-6), intermediate (6-20), or high (20+). Analysis included 80 clinically relevant driver mutations; genomic alterations known to confer a selective growth advantage. Of 723 brain tumors, TMB was low in 91.8%, intermediate in 6.1%, and high in 2.1%. When excluding tumor suppressor genes (TSGs), there was a trend toward decreased incidence of driver mutations in tumors with high TMB. Additionally, we determined that BRAF alterations were not identified in high TMB tumors, but were enriched in low TMB tumors. However, when including TSGs, 93% of tumors in the high TMB cohort harbored a driver mutation; 63% and 70% in the low and intermediate TMB cohorts, respectively. There is an association between high TMB and incidence of TSGs. In contrast, there is an association between low TMB and BRAF mutations. These represent populations in which ICPI may be more or less effective and further studies are needed.